Political Marketing And Barisan Nasional During The 13Th General Election (2013) In Penang - Koay, Hean Wei (2023)
Nowadays, voters are viewed as becoming more mature in making decisions, adversely leading to a political tsunami in Malaysia. This scenario is unpredictable and poses challenges for political parties to gain majority support. As a result, exploring the best political marketing methods for convincing voters is critical in Malaysia’s governance and political landscape. Using the Lees-Marshment Model as an analytical framework, this study focuses on the political marketing process and the model used by Barisan Nasional (BN) during the 13th General Election (GE13) in Penang. In-depth interviews with 18 informants from three BN political parties: UMNO, MCA, and Gerakan were conducted using semi-structured questions. Data from interviews were recorded andanalysed using Content Analysis. Surprisingly, the study’s main findings showed that the Lees-Marshment Model was not reflecting the political marketing trends employed by BN during GE13 in Penang. Based on the feedback received, this study introduces Chief-Oriented Product, a political marketing method primarily focused on the Chief or Party Leader. To sum up, the personality and behaviour of Party Leaders play a significant role in convincing voters in decision-making.